Estimation of Conjugated Linoleic Acid (CLA) Content in Ruminant Meat and Fats - Devatkal, Suresh; Kalpana, S.; Reddy , P. Baswa (Journal of Meat Science, 2019)
Conjugated linoleic acid (CLA) is a naturally occurring bioactive fatty acid in meat and fats of ruminant animals. CLA is gaining much  attention due to its nutritional and therapeutic properties. In this study, the presence of CLA in fat and muscle tissues of sheep, goat, and  buffalo was established. The CLA content of a large number of fat samples (N=140) was analyzed by measuring the UV-VIS absorbance  at 233 nm and comparing with the standard CLA absorbance curve. GC/FID and GC/MS were used for further used for quantification  and confirmation. Results showed a CLA concentration of 2.5 to 8.5 mg/g fat and 1.4 to 3.7 mg/g of meat in different ruminant species.  Further, rendered fat had a significantly (P
Keywords: Conjugated linoleic acid; Ruminant meat; GC-MS, Bioactive compound; Rendered fat